STUDENTS’ PERCEPTION OF USING THE AI GRAMMAR CHECKER APPLICATION IN LEARNING ENGLISH FOR HIGH SCHOOL STUDENTS - Nur Aini Agustina; Emeliya Sukma Dara Damanik (Indonesian EFL Journal, 2024)
The use of technology in education has become increasingly important in recent decades. One area where technology makes a significant contribution is in English language learning. English is an international language that is important to master in this era of globalization. High school students around the world are trying to improve their English skills in speaking, writing, reading, and listening. This research aims to explore Students’ Perception of using the AI Grammar Checker application in learning English for high school students. An exploratory qualitative research design was used to gain a comprehensive understanding of students' experiences with the AI Grammar Checker and its impact on their English learning. Data collection was carried out through in-depth interviews, questionnaires, and direct observation. The collected data was analyzed using a thematic analysis approach. The results showed that most students found the AI Grammar Checker application useful for improving their English grammar skills. However, some students felt that the recommendations provided by the application were sometimes irrelevant. While the majority reported a positive impact on their writing skills, some did not feel a significant effect. Overall, this research indicates that the AI Grammar Checker application has great potential for improving English learning for high school students. However, it is important to understand individual student needs and make adjustments in the use of the application to provide maximum benefits.